Shopaholic ties the knot - Kinsella, Sophie (Black Swan, 2002)
For once in Becky Bloomwood's life, things are going smoothly. She's got the dream job as a personal shopper (spending other people's money - and getting paid for it). She's got a fabulous Manhattan apartment with her boyfriend Luke. They've even opened a joint bank account (although they can't quite agree on whether a Miu Miu skirt counts as a household expense). Then Luke proposes - and all of a sudden life gets hectic. Becky's mum in rural Surrey wants one thing, Luke's mother in New York wants the complete opposite. Becky knows she has to sit down and decide - but to be honest, it's a lot more fun testing cake, trying on dresses and registering wedding presents. But time's ticking by, plans are being made both sides of the Atlantic and soon she realizes she's in trouble...